Studies of new piperazine-based "stimuli" responsive polymers and hydrogels - Roshandeen, G. (2008)
This thesis describes the studies of some new piperazine-based stimuli-responsive polymeric materials. The thesis is divided into two sections. The first section describes the synthesis and characterization of three new piperazine monomers, their homopolymers, copolymers and hydrogels. The homopolymers of N-acryloyl-N'-methyl piperazine (AcrNMP), N-acryloyl-N' -ethyl piperazine (AcrNEP) and N-acryloyl-N'-propyl piperazine (AcrNPP) were all highly soluble in water. Interestingly, only poly (AcrNPP) showed lower critical solution temperature (LCST) phenomenon with the phase transition temperature at 37 °C. Poly(AcrNEP) and poly (AcrNMP) were too soluble in water and no LCST were observed. However, the copolymers of methyl methacrylate (MMA) with AcrNMP and AcrNEP exhibited LCST phenomena due to increased hydrophobicity introduced by MM A. The phase transitions occurred at a wide range of temperatures depending on the compositions. The phase transitions were studied by dynamic light scattering (DLS), micro differential scanning (MDSC) and spectrophotometric methods. For the copolymerization of MM A with AcrNEP the reactivity ratios were evaluated. The values were n (AcrNEP) = 0.72 ± 0.07, and n(MMA) = 1.08 ± 0.04.